Medical Physics. - Mishkat Ali Jafri; Intikhab Ulfat (International Journal of Endorsing Health Science Research, 2023)
Medical physics is a branch of applied physics that is dedicated to the application of physics principles and techniques to the field of medicine. It plays a crucial role in ensuring the safety and effectiveness of medical procedures and contributes to advancements in the diagnosis and treatment of various medical conditions. Medical physics has its roots in the early discoveries of X-rays by Wilhelm Roentgen and the radioactive properties of certain elements, notably those discovered by Marie Curie.